Positive Affect, Negative Affect dan Kepuasan Upah Karyawan dalam Perspektif Signal Sensitivity - Muhammad Zaky (Universitas Islam Indonesia, 2006)
Wage is an important element in a company. For employes, wage reflects what they get from their service give to the company. Meanwhile it is, normally, a significant part of cost for most of company. This article highlights the importance of company to have a great attention on dispositional factors, such as positive affect (PA) and negative affect (NA)t, rather than situational factors in determining labor pay satisfaction. In the signal sensitivity perspective, dispositional factors give more deep information about pay satisfaction of the employee.Keywords: Positive affect (PA), negative affect (NA), pay satisfaction, signal sensitivity.